1977
DOI: 10.1055/s-0028-1094521
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Vigilance and Performance under Lithium-Treatment Studies in Patients and Normal Volunteers*

Abstract: Subtle changes of adaptive behaviour under lithium treatment may possess interest not only as side-effects, but also as a possible explanation for the mechanism of action of lithium salts. - In 18 patients under long-term lithium treatment and 10 normal volunteers before and after one week of lithium application the EEG was recorded and performance as well as psychophysiological tests were carried out. The results, particularly of the d-2-test point to a considerably reduced performance in patients and normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Fasting Cortisol Concentrations at 8 a.m. Platman and Fieve (1968), Platman et al (1971), Berens and Wolff (1975), Miiller-Oerlinghausen et al (1977), Halmi et al (1978), Czernik and Kleesiek (1979) did not observe any significant differences of basal cortisol plasma concentrations in lithium treated manic-depressive patients, although an initial, but transient rise after acute oral administration was evidenced.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Fasting Cortisol Concentrations at 8 a.m. Platman and Fieve (1968), Platman et al (1971), Berens and Wolff (1975), Miiller-Oerlinghausen et al (1977), Halmi et al (1978), Czernik and Kleesiek (1979) did not observe any significant differences of basal cortisol plasma concentrations in lithium treated manic-depressive patients, although an initial, but transient rise after acute oral administration was evidenced.…”
Section: Discussionmentioning
confidence: 91%
“…Although the role of the serotonergic system is far from being elucidated, there is converging evidence that it has homeostatic and pace maker functions (Aghajanian and Wang, 1978) as well as an important role in the circadian periodicity of ACTH and cortisol regulation (Miiller et aL, 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adaptive tracking task is a more refined pursuit and tracking test, which has been shown by Borland & Nicholson (1974) to be sensitive to the effects of heptabarbitone 200, 300 and 400 mg, and Nicholson (1979) has shown the residual sedative activity of flurazepam 30 mg, nitrazepam 10 mg, oxazepam 30 and 45 mg, temazepam 20 mg and diazepam 10 mg. Muller-Oerlinghausen, Bauer, Girke, Kanowski & Goncalves (1977) have also used adaptive tracking tests to detect the impairment of performance produced by lithium salts in both patient and volunteer populations. It is clear that adaptive tracking is a reliable index of the effects of sedative drugs.…”
Section: Motor Manipulationmentioning
confidence: 99%
“…Mueller-Ocrlinghausen et 114 Engelsmann/Ghadirian/Grof Lithium and Memory Assessment: Methodology al. [ 15] found that patients who had been on lithium treat ment for more than 3 years obtained vigilance and learn ing test scores significantly lower than standardized val ues. Shaw et al [13] used an on-off-on design (the so called B-A-B design), and administered a battery of psy chological tests to 22 euthymic out-patients with affective disorders in remission, during both lithium treatment and blind-placebo substitution.…”
Section: Cognition and Memorymentioning
confidence: 99%